2008
DOI: 10.1530/eje-08-0476
|View full text |Cite
|
Sign up to set email alerts
|

Multiple endocrine neoplasia type 2A in two families with the familial medullary thyroid carcinoma associated G533C mutation of the RET proto-oncogene

Abstract: Introduction: Multiple endocrine neoplasia type 2A (MEN2A) is an autosomal dominant hereditary disorder, associated with a cluster of germline gain-of-function mutations of the RET proto-oncogene (RET), mainly in exons 10-15. The G533C mutation in exon 8 of the RET is rare and has been mainly related to the familial medullary thyroid carcinoma. Patients-methods: We describe the RET G533C mutation in exon 8 of the RET in two unrelated female index patients, with MEN2A phenotype, consisting of pheochromocytoma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
0
33
0
2
Order By: Relevance
“…Codon 533 is located in exon 8 of the RET proto-oncogene, a region that is not routinely sequenced in most commercial laboratories in the United States offering RET analysis; therefore, patients with this mutation could easily be missed, which might account for its apparent rarity. Even though the majority of the 71 codon 533 patients came from a single large Brazilian family or from one of 5 different families of Greek ancestry (10,16,33,47), our data argue in favor of routinely sequencing exon 8, given that it is now a well-characterized and clearly deleterious mutation.…”
Section: Figmentioning
confidence: 80%
“…Codon 533 is located in exon 8 of the RET proto-oncogene, a region that is not routinely sequenced in most commercial laboratories in the United States offering RET analysis; therefore, patients with this mutation could easily be missed, which might account for its apparent rarity. Even though the majority of the 71 codon 533 patients came from a single large Brazilian family or from one of 5 different families of Greek ancestry (10,16,33,47), our data argue in favor of routinely sequencing exon 8, given that it is now a well-characterized and clearly deleterious mutation.…”
Section: Figmentioning
confidence: 80%
“…FMTC (OMIM*155240) is associated with mutations either in the extracellular or in the intracellular domain of RET, mostly affecting exons 10, 11, 13, 14 and 15 and never involving exon 16. Mutations in exons 5 and 8 have been reported respectively in one Czech family (8) and in five families originating from Brazil (9), Italy (10) and Greece (11)(12)(13). Nevertheless, the genetic analysis of these exons is routinely performed only in few centres, consistent with the very recent ATA guidelines for the management of MTCs (14), which include among the relevant exons of RET to be screened only exons 10 …”
Section: Introductionmentioning
confidence: 79%
“…It is also tempting to speculate that the high in vitro transforming potential found for this variant could be responsible for the aggressive behaviour of MTC with lung metastases found in patient 2. It is worth noting that another non-cysteine variant in RET exon 8 (Gly533Cys) has been described previously, but not functionally characterized, in five Greek families, three with MEN2A (11,13) and two with FMTC (12), and in one large Brazilian multigenerational family with FMTC (9). On the basis of all these data, exon 8 appears to be an underestimated hotspot of RET variants with an oncogenic potential.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the MTC was least aggressive as it was not clinically apparent, while none of the family members died from MTC-related causes. (Peppa 2008) Moreover, Kamakari et al, have identified the same G533C mutation in 11 unrelated families with FMTC and 4 with MEN2A, explaining the 'RET-negative' FMTC/MEN2A patients. .…”
Section: Diagnosis Of Medullary Thyroid Carcinomamentioning
confidence: 99%
“…(Schuffenecker 1998, Karga 1998 In addition, the same mutations are associated with significantly earlier progression from C-cell hyperplasia to MTC and earlier lymph node involvement than patients with most other mutations related to MEN2A and FMTC. (Peppa 2008, Hofstra 1994 According to the International RET Exon 10 Consortium, codon-associated penetrance by age 50, ranged from 60% (codon 611) to 86% (620) while more advanced stage and increasing risk of metastases correlated with mutation in codon position (609→620) near the juxtamembrane domain. 50%) family members.…”
Section: Diagnosis Of Medullary Thyroid Carcinomamentioning
confidence: 99%